New presentation about functional biomehanic of ileocecal valve - I. B. Kazantsev (Бюллетень сибирской медицины, 2011)
In spite of the fact that at present exists quite a few operative methodses, directed on reconstruction of insolvency lieocecal valve, united opinion, for functions given division of the bowels no. The aim of our study was to examine the biomechanics of the closer abilities of ileocecal valve, according to deep study of the anatomical forming the area ileocecal junction. In the course of studies was installed that in rate deskside ileocecal junction, external ligaments, pleats of the wall of the caecum, original musclearchitectonic, as well as geometry of the lips Bauhin’s dampers, play the important role in mechanism of the closing ileocecal valve.